Роль диалектизмов в рассказах Ф. Абрамова - Astrakhantseva A. A. (Interactive science, 2023)
Dialectisms. Linguistic features of dialects. The work of F. Abramov
Keywords: диалектизмы; Dialectisms. The dialect. Literary speech. The richness of the language; языковые особенности говоров; творчество Ф. Абрамова